Triumph over trash and other stories the ten outstanding Galing Pook Programs for 2008. ([Quezon City] Galing Pook Foundation, 2011)
The disc showcases the Galing Pook Awardees of 2008 and their innovative and excellent ways in the drive for the best public service to the Filipino people. The awardees include many organizations, government or non-government, who initiated change which challenges others to follow the proven innovative ways of development.
Governance as a shared responsibility : San Fernando City -- From ash to cash : Province of Pampanga -- Triumph over trash : transforming Payatas dumpsite : Quezon City -- Service efficiency in centralized warehousing : Marikina City -- The family townhouse project : Taguig City -- Steps ahead disaster : Province of Albay -- The sustainable city of San Carlos : San Carlos City, Negros Occidental -- An empowering barangay code : Barangay Sanito, Ipil, Zamboanga Sibugay -- Children of peace : Province of Cotabato -- Saving Allah Valley : Province of South Cotabato and Sultan Kudarat.
Title from label on disc.
Supplement to: Triumph over trash and other stories : the ten outstanding Galing Pook Programs for 2008 (KTRC-296).
Accompanying disc contains the text of the book in a multimedia eBook format.
Keywords: Local government -- Philippines -- Case studies; Local government -- Philippines -- Citizen participation -- Case studies; Community development -- Citizen participation -- Case studies; Land utilization -- Philippines